Pelatihan Pengelolaan Keuangan Rumah Tangga Mikro Pada Ibu-Ibu PKK Dengan Metode “COPLO” - Hendri Hermawan Adinugraha; Nafilah Nafilah; Ferida Rahmawati; Mila Sartika; Wikan Isthika; Hayu Wikan Kinasih; Melati Oktafiyani (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
The training program for micro-household financial management for peer-to-peer women using the “COPLO” method aims to provide explanations to PKK mothers about the urgency of planning and managing micro household finances, providing explanations to PKK mothers about the allocation of posts micro household finances that must be spent every month, starting from various sources of income to expenditure items, and providing training on the COPLO (Commitment to Envelope) method to make it easier for PKK mothers in managing micro household financial conditions every month . The results show that this program is very relevant to the conditions of partner needs in the field and can be implemented according to the planned event rundown. Based on the results of the evaluation of 30 participants who have participated in this activity, it can be concluded that there were 20 pre-activity people (66.67%) PKK RT. 05/06 women did not carry out directional financial management, and did not make an allocation of expenditure items each month. 90% of participants did not know about the COPLO (Commitment to Envelope) method related to household financial management. After the activity, the training participants began to understand the importance and benefits of allocating monthly expenditure items using the COPLO method, and participants began to try to apply the COPLO method for household financial management.